Real-time Selective Herbicide Applicator for Field Sugarcane - Thainimit, Somying; Muangkasem, Apimuk; Keinprasit, Rachaporn; Duangtanoo, Thanika; Tangwongkit, Rattana; Isshiki, Tsuyoshi (Agriculture and Natural Resources, 2012)
A system for a real-time selective herbicide applicator was developed. The system worked under natural light conditions without any assistant lighting device. A fast color-based weed detection technique was developed using a non-green subtraction procedure along with a conventional offset excessive green procedure. The experimental results showed that integrating these two techniques improves the robustness and weed detection accuracy of the system. In addition, the precision of the system was enhanced by increasing the command rates of the system controller. With the higher command rate, the number of detected weed groups was increased from 84.38 to 93.75%.